Pengaruh Fitur Layanan Aplikasi Mobile Banking terhadap Kepuasan Pengguna - Karmelia (International Journal Administration, Business & Organization, 2022)
Mobile banking are digital platforms that provide fast and secure access to banking services to meet users' financial needs. Through innovative features, these financial apps offer convenience in managing personal finances easily and efficiently. This research aims to determine the influence of features in mobile banking applications on user satisfaction, particularly in BCA's m-banking. The research methodology employed in this study is quantitative descriptive, utilizing questionnaire-based data collection. A total of 102 vocational students were involved in this research. Subsequently, data analysis was conducted using descriptive and regression analyses. The research findings revealed that the features in mobile banking applications have a positive and significant impact on user satisfaction.